Oncofinder, a new method for the analysis of intracellular signaling pathway activation using transcriptomic data - Buzdin, Anton A.; Zhavoronkov, Alex A.; Korzinkin, Mikhail B.; Venkova, Larisa S.; Zenin, Alexander A.; Smirnov, Philip Y.; Borisov, Nikolay M. (Frontiers in Genetics, 2014)
We propose a new biomathematical method, OncoFinder, for both quantitative and qualitative analysis of the intracellular signaling pathway activation (SPA). This method is universal and may be used for the analysis of any physiological, stress, malignancy and other perturbed conditions at the molecular level. In contrast to the other existing techniques for aggregation and generalization of the gene expression data for individual samples, we suggest to distinguish the positive/activator and negative/repressor role of every gene product in each pathway. We show that the relative importance of each gene product in a pathway can be assessed using kinetic models for “low-level” protein interactions. Although the importance factors for the pathway members cannot be so far established for most of the signaling pathways due to the lack of the required experimental data, we showed that ignoring these factors can be sometimes acceptable and that the simplified formula for SPA evaluation may be applied for many cases. We hope that due to its universal applicability, the method OncoFinder will be widely used by the researcher community.